Green Technologies Concepts, Methodologies, Tools and Applications - Information Resources Management Association (Information Science Reference, 2015)
This reference assembles the most up-to-date collection of research results and recent discoveries in environmental and green technology, including climate change, sustainable development, green diplomacy, and more"--Provided by publisher.